Mathematical modeling e-course - Deryusheva, V. N. specialist in the field of mechanical engineering Associate Professor of Tomsk Polytechnic University, Candidate of technical sciences 1982- (TPU Moodle, 2016)
In electronic course "Mathematical modeling" are described: the basic concepts of mathematical modeling; the methods of approximation, interpolation and prediction; modeling free vibration and applying vibration models; optimization. Particular attention is given devoted to the development of the skill to work in the environment of computer mathematics to solve engineering problems. The electronic course content considers the basic mathematical operations and work with matrices, studies the basic mathematical operations and work with matrices, deals with the solution of algebraic, differential equations and their systems, analyzes how to build 2D and 3D graphics, provides the methods of numerical integration and differentiation, etc. Knowledge of course "Mathematical modeling" will help in: determining the mathematical model based on experimental data; determining the intermediate values of the behavior of systems; the study of harmonic oscillations of different systems; solving optimization problems.